Intelligent Faraid Calculator Systems - Harith Hasyimi bin Hishamudin, Harith Hasyimi (Universiti Teknologi PETRONAS, 2012)
The Islamic Inheritance Law is a comprehensive inheritance distribution system. It covers all aspect of distribution of wealth such as how to distribute, to whom and what percentage to be distributed. It is very important for Muslim to learn about the Islamic Inheritance Law because they would face situations that require them to understand the distribution of wealth in the Islamic Law in one day. Hence, the author decides to share the knowledge of Islamic Inheritance Law using Intelligent Faraid Calculator system. The system is mainly proposed to provide the system that can help Muslims to calculate the distribution of wealth based on Islamic Law which most of the Muslim nowadays get confuse with the complexity of the calculation. The research on the system also is used to enhance the current system that being produced by USM student. Last but not least, the objective of the system is to educate the overall Muslims in planning the distribution of the wealth to their family members after they die.